Does Participation in 4-H Improve Schooling Outcomes? Evidence from Florida - Alfonso Flores-Lagunes; Troy Timko (Institute for the Study of Labor (IZA), 2014)
We examine the effect of participation in 4-H, the largest youth development program in the United States, on standardized test scores. We do this by utilizing grade-level longitudinal data on Florida's school districts from the Florida Department of Education combined with 4-H participation statistics from Florida 4-H. Specifically, we analyze the effect of the extent of 4-H participation for third through tenth grade on the mathematics and reading subtests of the Florida Comprehensive Assessment Test (FCAT). We use a difference-in-difference-in-differences (DDD) approach to control for potential confounders of the causal relationship at the level of school districts, grades, and years. Our results indicate that the extent of 4-H participation at the district-grade-year level is positively and significantly related to several measures of performance on the FCAT test.
Keywords: I21; I28; H52; 330; 4-H program; Florida; standardized test scores